Using Social Learning Networks (SLNs) in Higher Education: Edmodo Through the Lenses of Academics - Durak, Gürhan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
With its total number of users (around 62 million) throughout the world, it is important to determine the views of academics who use Edmodo (the leading SLN. In this respect in the first part of this two-part research, the purpose was to examine academics’ (n=50) use of technology and social networks. As for the purpose of the second part, it was to determine the views of 12 academics—selected from the academics participating in the first part—who had experience in Edmodo about the basic features of Edmodo and about its use in education. In the study carried out with the mixed method, the qualitative and quantitative data were collected with an online questionnaire. The findings obtained were interpreted within the framework of cooperative learning and the theories of “Diffusion of Innovations” and “Uses and Gratifications,” and the related themes were formed. As a result, the academics with experience in Edmodo reported their views about the benefits of use of the Edmodo in education. Regarding the differences between Edmodo and social networks, the results suggested that the former was used completely for educational purposes and that it did not involve any unnecessary components.